Black writers in Britain, 1760-1890 - Edwards, Paul, 1926-1992; Dabydeen, David (Early Black writers., 1991)
Containing extracts from all the major Afro-British writers and many early Black American, West African and Caribbean writers who spent time in Britain, this anthology is a sparkling introduction to the rich tradition of Black British writing. A general introduction to the anthology discusses the beginnings of Black literature in Britain during the period of Abolition. Each author in the anthology also has an individual introduction which briefly examines the author and the period in which he or she was writing, as well as the extract itself. The anthology is drawn from autobiographies, slave narratives, unpublished letters, oral accounts and public records, and represents the work of people such as Equiano, Cugoano, Sancho, Gronniosaw, Robert Wedderburn, James Africanus Horton, Mary Prince, Mary Seacole, Harriet Jacobus, Edward Wilmot Blyden and John E. Ocansey.